Marital sorting, inequality and the role of female labor supply: Evidence from East and West Germany - Pestel, Nico (Mannheim, 2015)
"This paper examines to what extent marital sorting affects cross-sectional earnings inequality in Germany over the past three decades, while explicitly taking into account labor supply choices. Using rich micro data, the observed distribution of couples' earnings is compared to a counterfactual of randomly matched spouses. Hypothetical earnings are predicted based on a structural model of household labor supply. For West Germany, a positive effect of marital sorting on inequality is found after adjusting for labor supply behavior, while the effect is limited when earnings are taken as given. This means that there is positive sorting in earnings potential which is veiled by relatively low female labor force participation. In East Germany, the impact of marital sorting on inequality is highly disequalizing irrespective of adjusting for labor supply choices. This is mainly due to the fact that East German women are much more attached to the labor market."